PENGARUH SUDUT KEMIRINGAN DAN LEBAR SUDU TERHADAP KINERJA TURBIN DARRIEUS DENGAN PROFIL SUDU NACA 0021 - Muhammad Abdul Kadir (KURVATEK, 2019)
Abstract                There are many low head hydro power energy  resources potential in Indonesia that have not been optimally in use. The main obstacles is that this kind of turbines have low pawer factor and low efficiencies. One of the low head hydro power turbines is Darrieus turbin. The excellence of Darrieus turbine is its simply and has high strength blades.  The verry important parameters that inflence to the turbine performance are width, angle of attack and cross section profile of the blades. The objective of the research is to investigate the influences of  blades width and blades  angle of attack to the  Darrieus turbine performance that using NACA0021 cross section blades. The research has been conducted in a three blades 20 cm diameter 25 cm length Darrieus turbine model. The blades width variations are 5 cm and 6 cm, and angle of attack variations are 00, 50, and 100. It is concluded from the research that the turbine maximum power output is 0.54083  Watt, maximum efficiency is 40.94 %, and maximum power factor is  0.2579 %. These values are reached at  5 cm blades width and 50 angle of inclination.Keywords : Darrieus turbine, NACA 0021,angle of attack, power, performance.